2017
DOI: 10.5194/soil-3-95-2017
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate retention capacity of milldam-impacted legacy sediments and relict A horizon soils

Abstract: Abstract. While eutrophication is often attributed to contemporary nutrient pollution, there is growing evidence that past practices, like the accumulation of legacy sediment behind historic milldams, are also important. Given their prevalence, there is a critical need to understand how N flows through, and is retained in, legacy sediments to improve predictions and management of N transport from uplands to streams in the context of climatic variability and land-use change. Our goal was to determine how nitrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 78 publications
3
8
0
Order By: Relevance
“…Our results are more consistent with authors who have observed reduced biological activity in buried organic‐rich horizons, especially in terms of denitrification (e.g. Koval 2011; Weitzman et al 2014; Weitzman & Kaye 2017). Clague et al (2013) cited less labile organic matter, low microbial biomass and diversity, and/or microbial communities without denitrifying genes as potential explanations for low denitrification capacity in buried historic organic soils compared to surface sediments.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are more consistent with authors who have observed reduced biological activity in buried organic‐rich horizons, especially in terms of denitrification (e.g. Koval 2011; Weitzman et al 2014; Weitzman & Kaye 2017). Clague et al (2013) cited less labile organic matter, low microbial biomass and diversity, and/or microbial communities without denitrifying genes as potential explanations for low denitrification capacity in buried historic organic soils compared to surface sediments.…”
Section: Discussionsupporting
confidence: 93%
“…This was based on well‐established studies indicating that denitrification is enhanced under saturated and anoxic soil conditions associated with near‐surface groundwater levels while nitrification is favored under well‐drained and oxic soil conditions (Burt & Pinay, 2005; Cirmo & McDonnell, 1997; Gold et al., 1998). This assessment was also supported by work of Weitzman and Kaye (2017) who reported elevated rates of nitrification in surficial and well‐drained riparian sediments and suggested these soils could serve as potential nitrate‐N sources for streams. The nitrification and N leaching rates could especially be elevated if riparian sediments contain buried organic‐rich soil layers which can be mineralized following drainage and oxidation (e.g., Gurwick, Groffman, et al., 2008, Gurwick, McCorkle, et al., 2008; Hill, 2011).…”
Section: Discussionsupporting
confidence: 71%
“…Fertilizer inputs associated with agricultural land uses in the White Clay Creek catchment may also contribute to legacy stores of exogenous solutes in soils. The presence of widespread legacy stores of NO 3 − and SO 4 2− , particularly if they are deep in the soil profile (Weitzman & Kaye, ), might explain the similar C‐Q behaviour of exogenous and geogenic solutes at both event and longer timescales. Similarities in the threshold behaviours of NO 3 − , SO 4 2− , and Cl − revealed by the piecewise regression analysis (Figure , Table ) further support the activation of deep source pools of these solutes in the White Clay Creek watershed.…”
Section: Discussionmentioning
confidence: 99%